A thermostability gel polymer electrolyte with electrospun nanofiber separator of organic F-doped poly-m-phenyleneisophthalamide for lithium-ion battery. (20th October 2016) - Kang, Weimin; Deng, Nanping; Ma, Xiaomin; Ju, Jingge; Li, Lei; Liu, Xiaohong; Cheng, Bowen
Abstract: In this study, the F-doped poly-m-phenyleneisophthalamide (PMIA) solution was synthesized by low temperature polymerization method and spun to be three-dimensional nanofibrous membranes by electrospinning. The Energy Dispersive X-Ray Spectroscopy and Fourier Transform Infrared Spectroscopy investigations verified that F was successfully doped in PMIA membrane. The X-ray diffraction patterns showed the crystallinity degree of PMIA membrane decreased with the addition of F. The morphology, pore size and aperture distribution tests manifested that the average diameter of F-PMIA fibers became finer and their distribution was more uniform than these of PMIA fibers. The electrolyte uptake, preserving liquid electrolyte, thermal stability and shrinkage resistance of the F-dopoed membrane were also significantly enhanced than that of pure PMIA membrane. The F-PMIA membrane could be acted as matrix to prepare gel polymer electrolyte. Finally, the F-doped PMIA membrane was used in the assembled coin cells to test the properties including the electronic conductivity, battery interfacial characteristics, electrochemical stability windows and cycle performances of battery. The lower electronic conductivity and interfacial resistance, higher electrochemical stability window (5.7 V) of F-doped PMIA membranes were obtained when comparing to the pure PMIA and commercial polyethylene membrane. The cell exhibited high first-cycle discharge capacity with 145 mAh g −1 and excellent cycling stability with good capacity retention of 93.1% and coulombic efficiency of 99.3% after 100 cycles.